MENUJU SATU TUBUH DENGAN BERBAGAI ANGGOTA - hendra winarjo (STT Amanat Agung, 2020)
Abstract: In this article, I propose an gesture for Indonesian Evangelicals to mediate conflicts that have the potential to arise due to the diversity of the church denominations in Indonesia by using a centered-set approach, not bounded-set approach, by placing five Evangelicals commitments at the center: (1) conversionism, (2) activism, (3) biblicism, (4) cruci-centrism, and (5) transdenominationalism. I argue that these five commitments should become the identity of Indonesian Evangelicals. By confessing these five commitments with a centered-set approach, Indonesian Evangelicals can set aside other and less basic commitments and differences from the various church denominations in Indonesia in order to live and work together. The main purpose of mediating the conflict that could potentially arise due to the diversity of church denominations here is to achieve a vision of one body with multiple members as the church described in the Bible (1 Cor. 12:12-27; Eph. 4:4, 16). To achieve the objectives of this article, I will first describe the context of the diversity of church denominations in Indonesia. Further, I will analyze the identity of Evangelicals in Indonesia and describe a centered-set approach for the attitudes of Indonesian Evangelicals in responding to the diversity of church denominations. Keywords: evangelicals, church denominations, christianity in Indonesia, church unity. Abstrak: Dalam artikel ini, penulis bertujuan untuk mengusulkan suatu sikap bagi kaum Injili Indonesia untuk memediasi konflik yang berpotensi muncul akibat keragaman denominasi gereja di Indonesia dengan menggunakan suatu pendekatan yang terpusat, bukan dengan pendekatan yang membatasi, yaitu dengan menaruh lima komitmen kaum Injili sebagai pusatnya: (1) conversionism, (2) activism, (3) biblicism, (4) cruci-centrism, dan (5) transdenominationalism. Penulis berargumen bahwa lima komitmen inilah yang semestinya menjadi identitas kaum Injili Indonesia. Dengan mengakui lima komitmen tersebut dengan pendekatan yang terpusat, kaum Injili Indonesia dapat menyampingkan komitmen-komitmen dan perbedaan-perbedaan yang lain dan kurang mendasar dari beragam denominasi gereja di Indonesia agar dapat hidup bersama dan bekerja sama. Tujuan utama dari memediasi konflik yang berpotensi muncul akibat keragaman denominasi gereja di sini adalah untuk menuju visi satu tubuh dengan berbagai anggota sebagaimana gereja yang digambarkan di dalam Alkitab (1Kor. 12:12-27; Ef. 4:4, 16). Untuk mencapai tujuan dalam tulisan ini, pertama penulis akan mendeskripsikan konteks keragaman denominasi gereja di Indonesia. Selanjutnya, penulis menganalisis identitas kaum Injili di Indonesia dan menjelaskan pendekatan yang terpusat bagi sikap kaum Injili Indonesia di dalam merespons keragaman denominasi gereja. Kata-kata kunci: kaum Injili, denominasi gereja, kekristenan di Indonesia, kesatuan gereja.